Exhibiting the Great Patriotic War in Soviet capitals: Moscow, Kyiv, Minsk - Free, Anya (Studia Rossica Posnaniensia, 2024)
During World War II, Soviet museums constituted an important part of the war propaganda machine and were used by the Soviet state to mobilize its population and to create a public historical narrative about the war. Staff at Soviet museums began organizing war-related patriotic exhibitions from the very first days of the German invasion in June 1941. This article focuses on two types of war-themed exhibitions and museums that were prominent in the Soviet urban spaces during the war and immediately after: trophy exhibitions and exhibitions and museums that focused on constructing historical narratives about the war. Among the main topics of the latter exhibitions were partisan resistance, German atrocities, and the central role of the Communist Party and Stalin personally. While the creators of these war museums adhered to the ideological frameworks and museum content plans developed by Moscow’s professional ideologists, I demonstrate that local museum workers were able, to some extent, to deviate from centrally prescribed narratives and to engage their own agency and creativity, and that the extent of this deviation was largely defined by regional specifics and by individual efforts and local circumstances. The impact of regional differences in the narration of the war is especially evident in the comparison of the representation of the Holocaust in museums in Kyiv and Minsk. Finally, I demonstrate that local circumstances were a major factor in the fate of each museum after the end of the war.